Women's Attitudes in Preparing for Menopause - Tri Ardayani Yani (Journal of health research and technology, 2026)
Menopause is the natural cessation of menstrual cycles in women as they age. The average age of menopause in Indonesia is between 45 and 55, and the proportion of menopausal women in the country is rising by about 3% annually. By 2025, there will likely be 60 million menopausal women in Indonesia. Using a literature review process, this study was written. The search terms "attitude," "readiness," and "menopausal women" were employed in the literature review search approach. Relevant resources, especially Google Scholar and PubMed, offered the information needed to look for studies both domestically and abroad. Articles must be in English or Indonesian, (1) original, (2) published in the last five years (2022–2025), and (3) fully accessible. Thirty domestic and international items were located, and articles published during the last five years but not fully accessible within that time frame satisfied the exclusion criteria. Following the preliminary review of abstracts, titles, and inclusion criteria, 30 journals were found. Following the discovery of twelve articles in the final step of screening based on processes and results, fifteen national articles were discovered in the second stage of screening, utilizing inclusion and exclusion criteria. Having a positive outlook might help women going through menopause turn negative emotions into positive ones or participate in worthwhile activities. To cope with menopause, women must be prepared on a physical, psychological, emotional, and spiritual level. Menopausal women can become more self-assured, think more positively, and embrace the reality of menopause by making these three preparations, which will boost their readiness and help them avoid the symptoms that occur throughout menopause. The degree to which women are prepared for menopause depends on their socioeconomic status, environment, and society.